PENGARUH ASAP ANTI NYAMUK KERTAS BAKAR TERHADAP JUMLAHERITROSIT PADA MENCIT (Mus musculus L.) - Choirun Niswah; Syarifah Syarifah; Fitria Sany (Jurnal SainHealth, 2018)
Indonesia is a tropical country encountered species of mosquitoes, such as Aedes aegypti and Culex quinquefasciatus. One of the efforts made to eradicate mosquitoes is to use mosquito repellent. Mosquito repellent is one type of insect killers household pesticide (insecticide) containing dangerous transfultrin. This study aims to determine the effect of anti-mosquito smoke burn paper against the number of erythrocytes in mice (Mus musculus L.). The study was conducted in September 2016 in the Laboratory of Mathematics of Tarbiyah and Teaching Faculty of UIN Raden Fatah Palembang. The research method using a completely randomized design (CRD) with treatment P0 (without exposure to insect repellent), P1 (anti mosquito burn paper, 2 hours / day), P2 (anti mosquito burn paper, 4 hours / day), P3 (anti mosquito burn paper, 6 hours / day) each with 6 replications, for 20 days. On the last day to do the stabbing in the tail to draw blood, were calculated against the number of red blood cells (erythrocytes) by using Haemocytometer. The results showed that exposure to fuel anti-mosquito burn paper affect the red blood cells of mice that P1 (anti mosquito burn paper, 2 hours / day) with an average of 8,72 x 106 / mL blood, P2 (anti mosquito burn paper, 4 hours / day) with an average of 8,87 x 106 / mL blood, P3 (anti mosquito burn paper, 6 hours / day) with an average of 7,89 x 106 / mL of blood. Effect of anti-mosquito smoke burn the most significant papers in a decrease in the number of erythrocytes of mice (Mus musculus L.) is 6 hours of exposure to an average of 7,89 x 106 / mL. The result of Anova test showed F count > Ftable namely 7,80 > 4,40 it means the treatment has significance.